Distributing Inheritance Before Death: Juridical Insights from Shafi'i Madhhab in Bangun Village - Rahman, Mhd. Kurnia; Hayati, Amal (JURNAL LEGALITAS, 2025)
This study investigates the practice of pre-mortem inheritance distribution in Bangun Village, Gunung Malela District, Simalungun Regency an emerging phenomenon driven by the intention to prevent family conflict. Despite its pragmatic rationale, this practice contradicts Islamic inheritance law as articulated in the Shafi'i Madhhab, which mandates that inheritance be distributed only after the testator’s death in accordance with faraid principles established in the Qur'an and Sunnah. Employing a qualitative design and an empirical juridical approach, this research draws on interviews with three local families (Mr. I, Mrs. R, and Mr. S), direct field observations, and a thorough analysis of primary Islamic legal texts and existing scholarly literature. The findings reveal a consistent pattern: inheritance is divided equally among heirs before the testator’s death, often without reference to the obligatory shares stipulated in Sharia. While intended to foster familial harmony, this informal practice risks undermining the legal structure of Islamic inheritance, potentially resulting in systemic injustice and intra-family disputes. The study's novelty lies in its empirical focus on a rural Muslim community's deviation from classical jurisprudence, an area rarely explored in existing literature. It also highlights an urgent need for community-based legal education tailored to Islamic inheritance law within the Shafi'i Madhhab. This research contributes to the discourse on legal pluralism, revealing the tension between local customs and normative Islamic law, and calls for integrative strategies to realign community practices with the ethical and juridical imperatives of the Qur’an and Sunnah.